Biliary tract perforation following percutaneous endobiliary radiofrequency ablation: A report of two cases - ZHOU, CHUANGUO (Oncol Lett, 2016)
Endobiliary radiofrequency ablation (RFA) has recently been recognized as a beneficial treatment option for malignant biliary obstruction using percutaneous or endoscopic approaches. The feasibility and safety of this method has been demonstrated in clinical studies, with pain, cholangitis and asymptomatic biochemical pancreatitis reported as relatively common complications. By contrast, hepatic coma, newly diagnosed left bundle branch block and partial liver infarction have been reported as uncommon complications. Biliary tract perforation is a serious potential complication of percutaneous intraductal RFA, which may result in severe infection, peritonitis or even mortality, and which has not been previously reported in clinical research. The current study presents the first reports of biliary tract perforation in two patients with unresectable malignant biliary obstruction following percutaneous intraductal RFA. Although the patient in case 1 succumbed 12 days after RFA, the minor biliary tract perforation in case 2 was successfully treated by the deployment of a self-expanding metal stent. This study demonstrates that biliary tract perforation should be recognized as a serious potential complication of endobiliary RFA, and that metal stent deployment should be considered as a treatment option for minor biliary tract perforation.